KONTRIBUSI LEMBAGA ADAT DALAM IMPLEMENTASI SYARIAT ISLAM DI ACEH - Abd. Wahid (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
During this time, the people of Aceh have used traditional institutions as one of the institutions to resolve various disputes that occur within the community. Because the majority of Acehnese people embraced Islam, then when the Islamic shari’ah was officially enforced, these traditional institutions could not be abandoned, even he strongly supported the implementation of Islamic sharia. This paper tries to examine the role of traditional Acehnese institutions as one of the institutions that has taken root in Acehnese society. In accordance with its characteristics, this research is a qualitative research with descriptive-analytical methods and normative-philosophical approaches. The results showed that the traditional institutions of Aceh had a certain role and authority in carrying out the settlement that occurred within the area (gampong / mukim) in Aceh. Customary institutions also have an influence on the establishment of Islamic Sharia, with provisions not contradicting the principles of Islamic law itself